ANALISIS PERKEMBANGAN KOGNITIF SISWA KELAS VIII SMP DALAM PROSES PEMBELAJARAN DI SMPN 4 KOTA BLITAR - Nadia Dwi Insani; Muhammad Ardiansyah; Nezhatian Adi Firmansyah; Surayanah Surayanah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The gap in learning characteristics of early adolescents and the presence of psychosocial anxiety barriers in students in expressing critical arguments orally are the background of this research activity. These field operational problems trigger low levels of independent thinking independence, class passivity, and inefficiency in managing the duration of academic assignments periodically. The main focus of this scientific study is to analyze the profile of student cognitive development and map the instructional barriers felt by eighth-grade students at SMPN 4 Blitar City. The steps of the quantitative approach with a descriptive survey method are operated using a closed questionnaire instrument distribution model of a four-level Likert scale criteria. Sampling was carried out using a total sampling technique that reached 27 active respondents in a structured manner. The numerical data processing procedure was executed through descriptive statistical calculations of the percentage of response distribution. The quantitative findings empirically revealed that the cognitive development of the subjects was in the good category which is in line with the characteristics of Jean Piaget's formal operational stage, where the achievement of material understanding dominated with a percentage of strongly agree at 70.3 percent. However, the aspects of courage to ask questions and independence recorded a fairly high number of disagreements at 29.6 percent. The main conclusion confirms that contextual problem conditioning has proven to be reliable in boosting students' academic resilience. ABSTRAK Kesenjangan karakteristik belajar remaja awal serta adanya hambatan kecemasan psikososial siswa dalam mengekspresikan argumen kritis secara lisan melatarbelakangi kegiatan penelitian ini. Masalah operasional lapangan tersebut memicu rendahnya tingkat kemandirian berpikir mandiri, kepasifan kelas, serta inefisiensi pengelolaan durasi pengerjaan tugas akademik secara berkala. Fokus utama kajian ilmiah ini adalah menganalisis profil perkembangan kognitif siswa serta memetakan hambatan instruksional yang dirasakan siswa kelas delapan di SMPN 4 Kota Blitar. Langkah-langkah pendekatan kuantitatif dengan metode survei deskriptif ini dioperasikan menggunakan penyebaran instrumen kuesioner angket tertutup model kriteria skala Likert empat tingkat. Penarikan sampel dijalankan menggunakan teknik total sampling yang menjangkau sejumlah 27 responden aktif secara terstruktur. Prosedur pengolahan data numerik dieksekusi melalui penghitungan statistik deskriptif persentase sebaran jawaban. Temuan kuantitatif secara empiris menyingkap bahwa perkembangan kognitif subjek berada pada kategori baik yang selaras dengan karakteristik tahap operasional formal Jean Piaget, di mana capaian pemahaman materi mendominasi pada persentase sangat setuju sebesar 70,3 persen. Namun, aspek keberanian bertanya dan kemandirian mencatatkan angka penolakan tidak setuju yang cukup tinggi sebesar 29,6 persen. Simpulan utama menegaskan bahwa pengondisian masalah kontekstual terbukti andal mendongkrak ketahanan akademik siswa.